passive immunization with Candida albicans antiproteinase as a prophylactic tool against the candidiasis - Drshim, Azhar A.I.; Badr, rassool A; Badr, sand E. (Journal of the Faculty of Medicine Baghdad, 2005)
Summary: Background: life threating fungel disease is now a frequent substantial of the immunocomprimised host population . Candida infection has raised throughout the era of antibiotics & immunosuppressive chemotherapy. Aim of study : to highlight the need for alternative immunprophlactic tool .Therefore the need to develop prophylactic or therapeutic immunolglobulin against candidacies Materials & Methods: 12.5 mg/ml. of Candida albicans proteinase enzyme was injected S/C into a group of five rabbits weighing 3 Kg. with complete Freund’s adjuvant. Antisera was collected from the animals after 28 days . 0.2 ml of this antisera given l/V into two group of rabbits ; followed by 0.1 ml of the antiserum one of thses groups as control. the 21"1 group challenged with 2.8*10^7 cfu/ml of actively growing C. abicans for three days . the 3rd group received only 2,8*10A7 cfu/ml ofC. albicans for three days Results: Test rabbits , which received both antisera and C. albicans , were completely protected when examined after six weeks . No symptoms of the diaease ; no pathological lesions could be seen in the organs ( Kidneys, liver and spleen ). Culture for C. albicans from these organs were all negative . In contrast to rabbits received challenged dose of Candida; they become sick , visceral organs showed profuse microabscesses . Candida was isolated from minced organs on culture . Conclusion : the findings draws attention to an important fact that the passive immunizention can be applied to protect patients with leukemia and others immunocompromised individuals from serious infection of Candida . This discovery calles for application to open anew hope for these patients at least to diverse their suffer for sometime,